2013
DOI: 10.1063/1.4807171
|View full text |Cite
|
Sign up to set email alerts
|

A strong anisotropy of spin dephasing time of quasi-one dimensional electron gas in modulation-doped GaAs/AlGaAs wires

Abstract: We investigated the wire orientation dependence of ensemble electron spin dynamics by using a time-resolved Kerr rotation technique in wires made from a modulation-doped GaAs/AlGaAs quantum well. We observed a strong anisotropy of the electron spin dephasing time of as large as 40 depending on the wire orientation at 5 K by tuning the spin-orbit interaction. The wire width dependence of the spin dynamics is reproduced in a Monte Carlo simulation. In addition, two characteristic spin decay rates were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Thus, the spin information can propagate over a distance without relaxation. Experimental studies on 2DEGs in quantum wells (QWs) revealed the emergence of this PSH state, in which suppression of ensemble spin dephasing was examined, 12,13) and a spin texture was revealed by spatiotemporally resolved Kerr rotation microscopy. 14) In these cases, the well width and the doping profile (which determine Dresselhaus and Rashba SOI parameters) were pre-designed in samples.…”
mentioning
confidence: 99%
“…Thus, the spin information can propagate over a distance without relaxation. Experimental studies on 2DEGs in quantum wells (QWs) revealed the emergence of this PSH state, in which suppression of ensemble spin dephasing was examined, 12,13) and a spin texture was revealed by spatiotemporally resolved Kerr rotation microscopy. 14) In these cases, the well width and the doping profile (which determine Dresselhaus and Rashba SOI parameters) were pre-designed in samples.…”
mentioning
confidence: 99%
“…This leads to dephasing, 9,10 but not to precession of the net spin polarization. After local spin excitation, a spatially varying spin rotation can be resolved as exemplified for the spin helix case [11][12][13] and laterally confined wire structures. 14,15 Such a spatial mapping of the spin mode allows the determination of the SO parameters, but requires a spatial resolution better than the SO length.…”
mentioning
confidence: 99%
“…This anisotropy, which arises due to the interplay between the Rashba and Dresselhaus SO coupling strengths, could be estimated comparing the spin relaxation time for two distinct channel orientations. Finally, our model could also be used to study the anisotropy of the spin relaxation time [35] and its dependence on the width of the wire [36][37][38][39][40][41], even in the limit of a few-subband quantum wire when the semiclassical approximation is no longer valid.…”
Section: Discussionmentioning
confidence: 99%